2011
DOI: 10.1007/s00231-011-0919-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on heat transfer correlations of supercritical CO2 cooled in horizontal circular tubes

Abstract: The objective of the present study is to analyze the heat transfer correlations of supercritical CO 2 cooled in horizontal circular tubes. In the paper, heat transfer correlations are first reviewed and compared with the experimental data at different heat fluxes. The results show that most of the previous correlations agree well with the experimental data under lower heat flux, but fail to predict the heat transfer coefficient well when the heat flux is as high as 33 kW/m 2 . The study of buoyancy effect on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In 2012, Lin et al [73] reviewed the existing correlations for Nusselt number of sCO 2 cooled in horizontal tubes, concluding that correlations provide higher accuracy when the heat flux is lower and hence buoyance is weaker. On the other hand, for cases where the buoyancy effect is stronger, all correlations fail in determining the heat transfer coefficient accurately.…”
Section: Fcmentioning
confidence: 99%
“…In 2012, Lin et al [73] reviewed the existing correlations for Nusselt number of sCO 2 cooled in horizontal tubes, concluding that correlations provide higher accuracy when the heat flux is lower and hence buoyance is weaker. On the other hand, for cases where the buoyancy effect is stronger, all correlations fail in determining the heat transfer coefficient accurately.…”
Section: Fcmentioning
confidence: 99%
“…(8). Recently, Lin et al [11] tested the accuracy of the correlations by comparisons between the calculations and experimental data. Conclude that when the heat flux is lower, the buoyancy effect is comparably weaker, and most of the previous correlations agree well with the experimental data; when the heat flux is up to 33 kW m-2, the buoyancy effect becomes stronger, and the correlations fail to predict the heat transfer coefficients accurately.…”
Section: Correlations For Supercritical Co 2 Cooling In Macro-channelsmentioning
confidence: 99%
“…The influence of various factors (operating pressure, mass flow, tube diameter, wall temperature and buoyancy effect) on the sCO2 cooling mechanism and heat transfer deterioration under heating mode were comprehensively reviewed [122]. Numerous review studies were performed on proposed heat transfer correlations for sCO2 in different tube geometries [16,20,21,69,104,[142][143][144]. Vignarooban et al [145] reported the applicability of various molten salts, liquid metals, gas, thermal oil, and organic fluid as a working fluid in the central receiver of the CSP plant driving a sCO2 power block.…”
Section: Earlier Reviewmentioning
confidence: 99%
“…Further experimental investigations were suggested for better prediction of the wall and bulk temperatures. Lin et al [21] reviewed the various heat transfer correlations of sCO2 and performed the comparison of correlations with the experimental dataset. At significantly lower heat flux, most of the correlations showed better prediction while at higher heat flux, the buoyancy force became stronger and many of the existing correlations failed to predict the exact heat transfer mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation